KASB-HUNAR MAKTABLARIDA MATEMATIKA FANINING DOLZARBLIGI (Modern education and development, 2024)
Kasb-hunar maktablarida matematika o‘qitishning maqsadi quyidagi uch omil bilan belgilanadi: 1. Matematika o‘qitishning umum ta’limiy maqsadi. 2. Matematika o‘qitishning tarbiyaviy maqsadi. 3. Matematika o‘qitishning amaliy maqsadi. The purpose of teaching mathematics in vocational schools is determined by the following three factors: 1. General educational purpose of teaching mathematics. 2. Educational purpose of teaching mathematics. 3. Practical purpose of teaching mathematics.